Employees' job satisfaction and its influence on willingness to work in teams. - Benrazavi, Seyed Rahim; Silong, Abu Daud (North American Business Press, 2013)

(untitled)
This study examined the influence of employees’ satisfaction through achievement, recognition and nature of work towards their willingness to work in teams in order to reinforce the employees’ will towards working in teams. In this survey the relationship between the variables was tested among five major Malaysian organizations on the pathway of the theory of planned behavior. Herein, it was shown that the employees’ satisfaction towards their achievement, recognition received, and nature of work was positively related and motivational towards their willingness to work in teams. The study thus contributed to the process of organizing and human resource development in terms of willingness to work in teams.